2016
DOI: 10.1111/ssqu.12251
|View full text |Cite
|
Sign up to set email alerts
|

Operational Dynamics of Boko Haram's Terrorist Campaign Following Leadership Succession

Abstract: Objective This article analyzes the operational dynamics of Boko Haram, the largest radical Islamist organization engaged in acts of terrorism in Nigeria. Method We analyze Boko Haram's terrorist campaign using information gathered from 1,086 successful attacks that occurred between July 2009 and December 2014. We examine the operational tempo of attacks on a monthly basis, identify the primary tactics employed in and targets of those attacks, and assess the outcome of each successful attack in terms of severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 9 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Usually, victims of Boko Haram attacks include law enforcement agents, religious and political figures, essential infrastructures, and financial institutions and other business establishments. The strategic objectives of these attacks are to cast distrust of the Government in the minds of the people by making them feel vulnerable and unprotected by the Government (Regens, Mould, Vernon, & Montgomery, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Usually, victims of Boko Haram attacks include law enforcement agents, religious and political figures, essential infrastructures, and financial institutions and other business establishments. The strategic objectives of these attacks are to cast distrust of the Government in the minds of the people by making them feel vulnerable and unprotected by the Government (Regens, Mould, Vernon, & Montgomery, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that religious groups and institutions are sectors of society that have been negatively affected by the presence, actions and activities of the Boko Haram terrorist organization in the northeastern part of Nigeria and the greater Lake Chad region (Maiangwa et al 2012;Elden 2014;Onapajo and Usman 2015;Regens et al 2016). This is first because many of the radical clerics often use and interpret religious texts negatively, easily misleading and deceiving vulnerable persons into accepting their extremist views and teachings as the ultimate path to salvation (Maza et al 2020).…”
Section: What Are the Efforts Of Faith-based Organizations In Counter-radicalization In Nigeria: The Boko Haram Challenge?mentioning
confidence: 99%
“…Because countering terrorism is one of the major issues facing the intelligence community, this study employs information about real‐world events, rather than hypothetical scenarios, to illustrate the challenges associated with predicting future events using information derived from a collection of historical observations (Regens and Mould, ; Regens et al., , ). Specifically, we focus on predicting the actual operational dynamics of the Islamic State of Iraq and al‐Sham, commonly called ISIS ( ad‐Dawlah al‐Islmiyah ) or IS.…”
mentioning
confidence: 99%